Infographic. Stay physically active during COVID-19 with exercise as medicine - Wedig, I. J.; Duelge, T. A.; Elmer, S. J. (British Journal of Sports Medicine, 2021)
There are over 35 000 000 reported cases of COVID-19 disease and 1 000 000 deaths across more than 200 countries worldwide. With cases continuing to rise and a robust vaccine not yet available for safe and widespread delivery, lifestyle adaptations will be needed for the foreseeable future. As we try to contain the spread of the virus, adults are spending more time at home. Recent evidence suggests that physical activity levels have decreased by ~30% and sitting time has increased by ~30%. This is a major concern as physical inactivity and sedentary behaviour are risk factors for cardiovascular disease, obesity, cancer, diabetes, hypertension, bone and joint disease, depression and premature death.